Media Pengajaran Bahasa Arab dan Problematika Penerapannya Pondok Pesantren Darul Hikmah Lenggo-Lenggo - Ramli, Ramli; Takdir, Takdir; Luqmi, Zulfira; Azzahra, Nurul Fadhilah (Universitas Islam Ahmad Dahlan Sinjai, 2024)
The availability of teaching media and the ability and creativity of teachers in using them are important factors in teaching and learning Arabic language. So that this research identifies the availability of Arabic language teaching media at the Darul Hikmah Lenggo-Lenggo Islamic boarding school, and the ability and creativity of teachers in using them. This research uses a phenomenological (qualitative) approach. The data are collected by interview and observation, and then analyzed through several stages, namely: 1. Data reduction. Data obtained from observations, interviews and document studies were concluded through the researcher's interpretation. 2. Display data. The data collected are described in the form of categories. 3. Verify the data and make conclusion. At this stage, the data are categorized and then concluded. The results of this research show that the Arabic language teaching media at the Darul Hikma Lenggo-Lenggo Islamic boarding school is very limited. It only consists whiteboard, markers, erasers and arabic books. It is not found other technological media such as LCD and electronic media. The ability and the creativity of the arabic teachers in using teaching media is also very limited. It is caused by the lack of training in using the teaching media and a lack of references regarding the use of Arabic language teaching media.